African biblical studies and the question of methodology: A focus on New Testament scholarship in Nigeria - Uwaegbute, Kingsley I. (HTS teologiese studies, 2023)
African biblical studies (ABS) focus on biblical interpretation in Africa. Although new, it has gained massive recognition among African biblical scholars as the biblical interpretation focus that best suits the peculiar challenges that face African Christians. Its emergence, of course, was reactionary to the Western approach to the interpretation of the Bible in Africa and the practice of Christianity as well, which failed to take into cognisance the peculiar needs of African Christians. In New Testament scholarship in Nigeria, ABS has come to dominate biblical interpretation, being the most preferred by New Testament scholars. However, this article notices a persistent problem with regard to methodological rigour in ABS in Nigeria. This article aims to call the attention of New Testament scholars in Nigeria to methodological rigour while engaging in ABS as this is also part of the reasons breaking into mainstream New Testament scholarship has become a problem for many of these scholars. This equally leads to poor global visibility and competitiveness on the part of many Nigerian New Testament scholars. The approach to the discussion in the work is analytical and descriptive with a touch of personal observation.Contribution: This article calls attention to the need for ABS scholars in Nigeria to emphasise methodological rigour in their research. While this will lead to recognition of the works of ABS practitioners in Nigeria and beyond, this article makes a case for academic excellence which is the hallmark of good biblical scholarship.